The Effect Of Work Environment And Work Discipline On Employee Performance Through Emotional Intelligence - Sujila, Kristina; Prijati, Prijati; Santoso, Bambang Hadi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study aimed to find out and analyze the effect of work environment, work discipline, and emotional intelligence on the employees’ performance at the University of Nusa Nipa Indonesia. Besides, it aimed also to find out and analyze the effect of emotional intelligence in mediating the effect of work environment and work discipline on the employees’ performance at the University of Nusa Nipa Indonesia. Furthermore, the study was quantitative. The population was all employees at the University of Nusa Nipa Indonesia, consisting of 66 people. Moreover, the data were collected through questionnaires and analyzed descriptively with SPSS and T-Sobel. Additionally, the result of the descriptive analysis showed that the work environment, work discipline, emotional intelligence, and the employees’ performance were good criteria. In addition, the result of the path analysis concluded that 1) work environment affected employees’ performance, 2) work discipline affected employees’ performance, 3) emotional intelligence affected employees’ performance, 4) emotional intelligence was able to mediate the relationship of work environment on employees’ performance, and 5) emotional intelligence was able to mediate the relationship of work discipline on employees’ performance.